2017
DOI: 10.1016/j.jacl.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein insulin resistance score and risk of incident diabetes during extended follow-up of 20 years: The Women's Health Study

Abstract: Background Type 2 diabetes (T2D) is preceded by prolonged insulin resistance and relative insulin deficiency incompletely captured by glucose metabolism parameters, HDL-c and triglycerides. Objective Whether lipoprotein insulin resistance score (LPIR), a metabolomic marker, is associated with incident diabetes and improve risk reclassification over traditional markers on extended follow up. Methods Among 25,925 non-diabetic women aged 45 years or older, LPIR was measured by nuclear magnetic resonance spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…This is due to the very broad generalizability of our findings as euthyroid and SCT women comprise 97.3% of middle aged women in the United States (1). Previous studies have found strong associations for LPIR with incident T2D (20, 21), and also in the current WHS study population (22). The robust association between thyroid and LPIR may be a pathophysiological pathway of its hypofunction towards T2D.…”
Section: Discussionsupporting
confidence: 64%
“…This is due to the very broad generalizability of our findings as euthyroid and SCT women comprise 97.3% of middle aged women in the United States (1). Previous studies have found strong associations for LPIR with incident T2D (20, 21), and also in the current WHS study population (22). The robust association between thyroid and LPIR may be a pathophysiological pathway of its hypofunction towards T2D.…”
Section: Discussionsupporting
confidence: 64%
“…The post-smoothie VLDL particle AUC showed a tendency towards decreased triglyceride-enriched large VLDL particle AUC (P < 0.06; Table 3), balanced by an increase of the fewer triglyceriderich, medium VLDL particle AUC (P < 0.04, Table 3). A significant decrease in the lipoprotein insulin resistance score AUC, an NMR lipid analysis-based and validated method to assess insulin resistance, 17 was observed with walnuts (P < 0.01; Table 3). The large HDL particle AUC significantly increased in the walnut diet (P < 0.01; Table 3 and Figure S2).…”
Section: Effects Of Walnut Consumption On Lipid Fractionation and Bmentioning
confidence: 99%
“…Of further note, we observed a hitherto unreported rise in total plasma BCAA after ADX. Given that the LP-IR scores [16][17][18] and BCAA concentrations [20] have been shown to predict incident diabetes in population-based cohort studies, our present findings suggest that the risk of future diabetes development is not ameliorated and could even be worsened in PA patients without T2D initially despite remission of hyperaldosteronism after unilateral ADX.…”
Section: Discussionmentioning
confidence: 66%
“…LP-IR scores are closely related to glucose disposal measured with the hyperinsulinemic-euglycemic clamp technique and are strongly correlated with homeostasis model assessment of insulin resistance (HOMA-IR) [15,16]. Both the LP-IR and the plasma total BCAA concentration have been found to predict incident T2D in several population studies [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%